The Effect of Fermentation Time Variation on Antioxidant Activity of Fermented Robusta Coffee Leaves (Coffea canephora Pierre ex A.Froehner) Brew - Lisda Rimayani Nasution; Devi Agripina Saragi; Yade Metri Permata (Talenta Publisher, 2023)
Antioxidants are electron-donor compounds that can delay, slow down and prevent free radical reactions. Fermentation is a chemical change that occurs due to the activity of microorganisms which can increase the amount of phenols in tea thereby increasing its antioxidant activity. Fermentation is carried out with the help of a Symbiotic Culture of Bacteria and Yeast (SCOBY) culture, which is commonly used in the production of kombucha. Kombucha is a fermented tea drink produced from leaves that contain high phenols such as robusta coffee leaves (Coffea canephora Pierre ex A.Froehner). Factors that affect the fermentation process are pH and fermentation time. This study aimed to explain the effect of fermentation time on the antioxidant activity of fermented robusta coffee leaves brew. Brewed robusta coffee leaves were made by brewing robusta coffee leaves simplicia powder, adding kombucha liquid starter, then fermented for 0; 3; 7; 14; and 21 days, then pH and antioxidant activity was measured using UV-Visible spectrophotometer using the 2,2-dipheny-1,1-picrylhydrazyl (DPPH) at a wavelength of 516 nm. This study showed that 0; 3; 7; 14; and 21 days fermented robusta coffee leaves brew have pH of 6,07; 4,62; 4,07; 3,21; and 2,74, and IC50 values is 285,1645 Î¼g/ml; 219,7012 Î¼g/ml; 192,2325 Î¼g/ml; 187,0434 Î¼g/ml; and 173,9249 Âµg/ml. There is an effect of fermentation time variation on the antioxidant activity of fermented robusta coffee leaves brew. Keyword: Antioxidant, Fermentation, pH, Robusta coffee leaves, Time variation